Genetic Variation For Some Morphological Characters In Desi Cotton (Gossypium Arboreum L.) (Applied Biological Research, 2017)
The present investigation was carried out to assess genetic variation for some  easily observable traits in a set of 64 germplasm lines of Asiatic cotton  (Gossypium arboreum L.). The morphological characters included plant body  colour, colour of petals and anthers, leaf shape and presence/absence of leaf nectary. Green plant colour, yellow petal and anther colour, digitate leaf  shape, and absence of nectary were observed to be predominant  morphological characters among the desi cotton lines studied. Of the 64 cotton  genotypes evaluated, 56 were observed to have green and eight pigmented  plants. Desi cotton genotypes exhibited following petal colours: yellow (38),  white (13), variegated (7), cream (4), red (1) and off-white (1). Majority of the  genotypes (59) possessed digitate (narrow lobed) leaves. The present study has  provided an insight into the genetic variation for some morphological  characters in desi cotton genotypes. Though morphological markers have their  own limitations, yet these traits being independent of the effects of  environment, may be used for the identification of cotton germplasm  especially in seed production plots.
Keywords: Gossypium arboreum; leaf shape; nectarines; petal colour; pollen